Novel recombinant avian infectious bronchitis viruses from chickens in Korea, 2019–2021 - Kim, Hyun-Jin; Lee, Hyuk-Chae; Cho, Andrew Y.; Choi, Yun-Jeong; Lee, Heesu; Lee, Dong-Hun; Song, Chang-Seon (Frontiers in Veterinary Science, 2023)
Infectious bronchitis virus (IBV) has evolved through various mutation mechanisms, including antigenic drift and recombination. Four genotypic lineages of IBVs including GI-15, GI-16, GI-19, and GVI-1 have been reported in Korea. In this study, we isolated two IBVs from chicken farms, designated IBV/Korea/289/2019 (K289/19) and IBV/Korea/163/2021 (K163/21), which are two distinct natural recombinant viruses most likely produced by genetic reassortment between the S1 gene of K40/09 strain (GI-19 lineage) and IBV/Korea/48/2020 (GI-15 lineage) in co-infected commercial chickens. Comparative sequence analysis of hypervariable regions (HVRs) revealed that the K289/19 virus had similar HVR I and II with the K40/09 virus (100% and 99.2% nucleotide sequence identity, respectively), and HVR III with the IBV/Korea/48/2020 virus (100% nucleotide sequence identity). In contrast, the K163/21 virus had HVR I and II similar to the IBV/Korea/48/2020 virus (99.1% and 99.3% nucleotide sequence identity, respectively), and HVR III to the K40/09 virus (96.6% nucleotide sequence identity). The K289/19 virus exhibited similar histopathologic lesions, tissue tropism in trachea and kidney, and antigenicity with the parental K40/09 virus. The K163/21 exhibited similar pathogenicity and tissue tropism with the K40/09 virus, which were similar results with the isolate K289/19. However, it showed a lower antigenic relatedness with both parental strains, exhibiting R-value of 25 and 42, respectively. The continued emergence of the novel reassortant IBVs suggests that multiple recombination events have occurred between different genotypes within Korea. These results suggest that antigenic profiles could be altered through natural recombination in the field, complicating the antigenic match of vaccine strains to field strains. Enhanced surveillance and research into the characteristics of newly emerging IBVs should be carried out to establish effective countermeasures.